FOOD BASKETS DAN EDUKASI KESEHATAN LINGKUNGAN DALAM PENINGKATAN GIZI PENDERITA TUBERKULOSIS PARU DI KOTA MEDAN - Novrika Silalahi; Pitto Pratiwi Malau; Elmina Tampubolon; Rizka Annisa (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2025)
Pulmonary tuberculosis (TB) remains a major public health problem in Indonesia, including in Medan City. Malnutrition among TB patients worsens prognosis and delays recovery. Nutrition-based interventions such as Food Baskets combined with environmental health education are expected to improve nutritional status while preventing TB transmission at the household level. This study applied a quasi-experimental design with a pre-post test control group. A total of 30 pulmonary TB patients were enrolled and divided into an intervention group (n=15; received Food Baskets + environmental health education) and a control group (n=15; standard care). Data collected included body weight, energy intake, protein intake, hemoglobin, albumin, knowledge score, and environmental health behavior score. Data were analyzed using paired t-tests and independent t-tests, with significance set at p < 0.05. The intervention group showed a significant increase in body weight (+2.6 ± 0.9 kg) compared to the control group (+1.0 ± 0.8 kg, p < 0.001). Energy intake increased by +370 kcal/day in the intervention group versus +110 kcal/day in the control (p < 0.001). Protein intake increased by +15 g/day in the intervention group versus +4 g/day in the control (p < 0.001). Knowledge scores improved from 58 to 82, while environmental health behavior scores increased from 60 to 83 (p < 0.001). Food Baskets combined with environmental health education are proven effective in improving nutritional status, knowledge, and health behavior of pulmonary TB patients. This intervention can serve as an additional strategy in community-based TB control programs.